CLEAN WATER AND DIRTY WATER PLUMBING PLANNING AT DELIVERY CENTER POS MEDAN OFFICE - Ali; M. Aldianto; M. Davin; Fadhil N (Jurnal Dinamika Vokasional Teknik Mesin, 2025)
The construction of multi-story buildings requires comprehensive sanitation planning, including the design of clean water supply and wastewater drainage systems. Plumbing system planning aims to ensure that the supply of clean water and the disposal of wastewater are managed effectively and in accordance with technical standards. This study aims to analyze the clean water and wastewater plumbing installation requirements for the Pos Medan Delivery Center Office Building. The planning is based on the Indonesian National Standard 03-7065-2005, which outlines the procedures for plumbing system design. The clean water source is provided by deep well, which supplies water that is pumped into a rooftop storage tank. From there, water is distributed to each plumbing fixture using a gravity-fed system. Based on the planning calculations, the daily water demand for 77 employees is 4.62 m³/day. The estimated volume of blackwater (wastewater) generated is 3.12 m³/day, while the volume of greywater is 1.68 m³/day. The clean water piping system utilizes Polyvinyl Chloride pipes with the following dimensions ½ inch for individual plumbing fixtures, ¾ inch for distribution to 2–3 fixtures, 1 inch for distribution to 3–4 fixtures, 1¼ inch for distribution to 4–5 fixtures, 1½ inch for vertical risers and distribution to 5 or more fixtures. For the greywater and blackwater piping system, PVC pipes are also used with the following dimensions 1½ inch for discharge from washbasins, 2 inch for discharge from urinals, 2½ inch for floor drain discharge, 3 inch for vertical stacks collecting greywater from floor drains, washbasins, and sinks, 4 inch for toilet discharge, 6 inch for the main discharge line carrying blackwater from urinals and toilets to the bioseptic tank. This plumbing system design ensures an efficient and standardized distribution and disposal network, supporting the overall functionality and hygiene of the building.